2012
DOI: 10.3109/0142159x.2012.656755
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and correlates of depressive symptoms from an Arabian setting: A wake up call

Abstract: It has been shown that medical students have a higher rate of depressive symptoms than the general population and age- and sex-matched peers. This study aimed to estimate the prevalence of depressive symptoms among the medical students of a large school following a traditional curriculum and its relation to personal background variables. A descriptive-analytic, cross-sectional study was conducted in a medical school in Riyadh, Saudi Arabia. The medical students of King Saud University in Riyadh, Saudi Arabia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 24 publications
7
49
1
2
Order By: Relevance
“…We should not be surprised that our learners are so externally motivated or are not engaged in their role as a learner. Teacher-centred programmes are associated with a poorer learning climate and more depressive systems and burnout [37]. The same is true for learners in the workplace [38].…”
Section: Areas Of Evidencementioning
confidence: 99%
“…We should not be surprised that our learners are so externally motivated or are not engaged in their role as a learner. Teacher-centred programmes are associated with a poorer learning climate and more depressive systems and burnout [37]. The same is true for learners in the workplace [38].…”
Section: Areas Of Evidencementioning
confidence: 99%
“…Durante o internato, as angústias se intensificam. Incertezas na aplicação dos conhecimentos adquiridos, contato direto com o paciente, longos e exaustivos plantões, redução do tempo livre e a dificuldade na escolha da especialidade médica são alguns dos fatores que os estudos apontam para explicar a maior presença de sintomas de ansiedade e depressão no último ano da faculdade (Al-Faris et al, 2012;Benevides-Pereira & Gonçalves, 2009;Costa et al, 2012;Leão, Martins, Menezes, & Bellodi, 2011;Millan & Arruda, 2008;Yussuf, Issa, Ajiboye, & Buhari, 2013).…”
Section: Introductionunclassified
“…The prevalence of depression was different among King Saud University students, it was 48.2% divided into mild (21%), moderate (17%) and severe (11%) [2]. Another study showed a positive correlation between depression and anxiety among 450 female medical students at King Abdulaziz University, depression percentage found to be 14.7% while anxiety was 34.9%, considering the depression as the first predictor of morbid anxiety [3].…”
Section: Introductionmentioning
confidence: 99%